Visualization of powerful optical beam propagation in nonlinear mediums - Galkin, P.A.; Zhileikin, Ya.M. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
The results of numerical simulation of phenomena related to propagation of powerful optical beams in nonlinear mediums are discussed. A model of the nonlinear Schr&oumldinger equation is used. Much attention is given to the visualization of these results, which allows us to represent the nonlinear optical processes in visually evident and informative form.